2018
DOI: 10.1021/acs.chemmater.8b03542
|View full text |Cite
|
Sign up to set email alerts
|

Rb3SiF7:Mn4+ and Rb2CsSiF7:Mn4+ Red-Emitting Phosphors with a Faster Decay Rate

Abstract: A narrow-band red emission is a seminal issue for establishing the color-rendering index and color gamut of phosphor-converted white light emitting diode (pc-WLED) applications. In this regard, Mn 4+ -activated K 2 SiF 6 phosphors (referred to as K216) have recently attracted a great deal of attention after their successful commercialization. As with K216 phosphors, Mn 4+ -activated K 3 SiF 7 (referred to as K317) phosphors perform in a manner that is similar to that of K216 phosphors and have been introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…44,45 Under excitation at 358 nm, the BGT:0.6%Mn 4+ sample exhibited an intense deep-red emission band in the wavelength range of 620–800 nm, with three emission peaks at 662, 674, and 688 nm, which can be assigned to the spin-forbidden 2 E g → 4 A 2g transition of the Mn 4+ ions. 46,47 Among these emission peaks, the 688 nm emission peak showed the strongest intensity. Figure 4b shows the Commission Internationale de l’Éclairage (CIE) diagram of BGT:0.6%Mn 4+ phosphors.…”
Section: Resultsmentioning
confidence: 99%
“…44,45 Under excitation at 358 nm, the BGT:0.6%Mn 4+ sample exhibited an intense deep-red emission band in the wavelength range of 620–800 nm, with three emission peaks at 662, 674, and 688 nm, which can be assigned to the spin-forbidden 2 E g → 4 A 2g transition of the Mn 4+ ions. 46,47 Among these emission peaks, the 688 nm emission peak showed the strongest intensity. Figure 4b shows the Commission Internationale de l’Éclairage (CIE) diagram of BGT:0.6%Mn 4+ phosphors.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphor-converted light-emitting diodes (pc-LEDs) are widely incorporated in everyday applications as a result of their environmental friendliness, low cost, and long life stability. Advancements in solid-state lighting are facilitated by material discovery; using high-throughput approaches, structural design as informed by density functional theory calculations targeting property optimization has already reduced the size of conventional LEDs to micro and mini, enabling the visualization of colors with finer contrast for backlighting applications. This pc-LED technology also finds use as an alternative light source for still-developing compact NIR applications including spectroscopy, health monitoring, biomodulation, bioimaging, plant growth, night vision, and anticounterfeit identification. In such NIR devices, NIR-emitting phosphors are encapsulated over blue LEDs, with the final performance almost solely dependent on the phosphors . Accordingly, NIR-emitting luminescence materials with high efficiency and good thermal properties are in increasing demand.…”
Section: Introductionmentioning
confidence: 99%
“…Given the exposed outer electron in 3d 3 electronic configuration of Mn 4+ ions, its optical property is sensitive to the coordination environment of host matrix . Some previous studies have confirmed that Mn 4+ ions preferentially reside in octahedral crystallographic sites except for several special cases . Many fluoride systems could well satisfy this structural requirement for Mn 4+ ions, and thus they are extensively developed as red‐emitting phosphors in white light‐emitting diodes (w‐LEDs).…”
Section: Introductionmentioning
confidence: 99%